Ceruloplasmin replacement therapy ameliorates neurological symptoms in a preclinical model of aceruloplasminemia. Issue 1 (28th November 2017) - Zanardi, Alan; Conti, Antonio; Cremonesi, Marco; D'Adamo, Patrizia; Gilberti, Enrica; Apostoli, Pietro; Cannistraci, Carlo Vittorio; Piperno, Alberto; David, Samuel; Alessio, Massimo
Abstract: Aceruloplasminemia is a monogenic disease caused by mutations in the ceruloplasmin gene that result in loss of protein ferroxidase activity. Ceruloplasmin plays a role in iron homeostasis, and its activity impairment leads to iron accumulation in liver, pancreas, and brain. Iron deposition promotes diabetes, retinal degeneration, and progressive neurodegeneration. Current therapies mainly based on iron chelation, partially control systemic iron deposition but are ineffective on neurodegeneration. We investigated the potential of ceruloplasmin replacement therapy in reducing the neurological pathology in the ceruloplasmin‐knockout (CpKO) mouse model of aceruloplasminemia. CpKO mice were intraperitoneal administered for 2 months with human ceruloplasmin that was able to enter the brain inducing replacement of the protein levels and rescue of ferroxidase activity. Ceruloplasmin‐treated mice showed amelioration of motor incoordination that was associated with diminished loss of Purkinje neurons and reduced brain iron deposition, in particular in the choroid plexus. Computational analysis showed that ceruloplasmin‐treated CpKO mice share a similar pattern with wild‐type animals, highlighting the efficacy of the therapy. These data suggest that enzyme replacement therapy may be a promising strategy for the treatment of aceruloplasminemia. Synopsis: Aceruloplasminemia (Acp) is a rare genetic disease caused by absence of ceruloplasmin (Cp) ferroxidase activity, which leads to iron accumulation in viscera and brain, inducing inter alia neurodegeneration. Cp replacement therapy is shown as a promising therapeutic avenue in the treatment of Acp. Two months treatment with human Cp allowed the protein to accumulate in the brain, where it exerted ferroxidase activity. Cp administration reduced the total iron content in the whole brain, and the iron accumulation found in choroid plexus epithelium. The treatment with Cp prevented the loss of Purkinje cells in the cerebellum. An improvement in motor coordination was observed at the end of Cp treatment. Cp replacement therapy was able to ameliorate the neurological symptoms and could be a promising treatment also in human aceruloplasminemia. Abstract : Aceruloplasminemia (Acp) is a rare genetic disease caused by absence of ceruloplasmin (Cp) ferroxidase activity, which leads to iron accumulation in viscera and brain, inducing inter alia neurodegeneration. Cp replacement therapy is shown as a promising therapeutic avenue in the treatment of Acp.